Structural expression of bovine milk and meat factors in tissues of colorectal, lung and pancreatic cancer patients: infectious causes of cancer : short report - Nikitina, Ekaterina; Alikhanyan, Kristina; Neßling, Michelle; Richter, Karsten; Kaden, Sylvia; Ernst, Claudia; Seitz, Stefan; Chuprikova, Liubov; Häfele, Lisa; Gunst, Karin; Rahbari, Nuh Nabi; Birgin, Emrullah; et al. (International journal of cancer, 2023)
Chronic inflammation, linked to the presence of bovine milk and meat factors (BMMFs) and specific subsets of macrophages, results in oxygen radical synthesis and induction of mutations in DNA of actively replicating cells and replicating single stranded DNA. Cancers arising from this process have been characterized as indirect carcinogenesis by infectious agents (without persistence of genes of the agent in premalignant or cancers cells). Here, we investigate structural properties of pleomorphic vesicles, regularly identified by staining peritumor tissues of colorectal, lung and pancreatic cancer for expression of BMMF Rep. The latter represents a subgroup of BMMF1 proteins involved in replication of small single-stranded circular plasmids of BMMF, but most likely also contributing to pleomorphic vesicular structures found in the periphery of colorectal, lung and pancreatic cancers. Structurally dense regions are demonstrated in preselected areas of colorectal cancer, after staining with monoclonal antibodies against BMMF1 Rep. Similar structures were observed in human embryonic cells (HEK293TT) overexpressing Rep. These data suggest that Rep or Rep isoforms contribute to the structural formation of vesicles.
Erstmals veröffentlicht: 28. November 2022
Gesehen am 15.07.2024